Totalidade existencial e mundo como totalidade: o conceito de totalidade na ontologia fundamental de Martin Heidegger - Flores, Juliana Mezzomo (2009)
The attendant work advances as a central goal the inquiry into Martin Heidegger s approach to the concept of totality. In this purpose we bound this interpretation within the period from 1927 to 1930, focusing on the works Being and Time, What is Metaphysics? and The Fundamental Concepts of Metaphysics: world, finitude and solitude. Starting with the reconstruction of the concept of totality in Being and Time, we seek to make clear the bearing of the theory about parts and wholes in the E. Husserl s 3º Logical Investigations. We shall argue that the influence of hursselian mereology takes place within two wide ranges of the heideggerian ontological inquiry: a) in the structuring of the analytic of being there and b) the problem formulation concerning the possible totality for human entity conceived as existence. Subsequently, this concept will be examined in writings such as The Fundamental Concepts of Metaphysics and What is Metaphysics?, having as focus the elucidation of the notion of being as a whole . Finally, we will approach the concept of totality in Being and Time and The Fundamental Concepts under a specific viewpoint: the problems linked to the concept of world in the works from 1927 and 1929.